2016
DOI: 10.1210/en.2016-1282
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Chronodisruption Impairs Circadian Physiology in Rat Male Offspring, Increasing the Risk of Chronic Disease

Abstract: Chronic exposure to light at night, as in shift work, alters biological clocks (chronodisruption), negatively impacting pregnancy outcome in humans. Actually the interaction of maternal and fetal circadian systems could be a key factor determining a fitting health in adults. We propose that chronic photoperiod shift (CPS) during pregnancy alter maternal circadian rhythms and impair circadian physiology in the adult offspring, increasing health risks. Pregnant rats were exposed to normal photoperiod (12 h light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
152
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(178 citation statements)
references
References 48 publications
18
152
3
5
Order By: Relevance
“…Taken together, these studies suggest that the light/ dark cycling itself may have an important role in development compared to constant conditions. Mendez et al (2016) report profound effects on maternal rat dams following chronic phase shift exposure during pregnancy, similar to those reported by Varoce and colleagues (Mendez et al, 2016;Varcoe et al, 2013Varcoe et al, , 2011. These include changes to the temporal organisation of physiology, endocrinology, and metabolism in offspring raised to 90 days in 12:12 LD.…”
Section: Overall Potential For the Validity Of Pliccsanimal Studies Csupporting
confidence: 79%
See 2 more Smart Citations
“…Taken together, these studies suggest that the light/ dark cycling itself may have an important role in development compared to constant conditions. Mendez et al (2016) report profound effects on maternal rat dams following chronic phase shift exposure during pregnancy, similar to those reported by Varoce and colleagues (Mendez et al, 2016;Varcoe et al, 2013Varcoe et al, , 2011. These include changes to the temporal organisation of physiology, endocrinology, and metabolism in offspring raised to 90 days in 12:12 LD.…”
Section: Overall Potential For the Validity Of Pliccsanimal Studies Csupporting
confidence: 79%
“…Metabolic changes include no observable circadian rhythm for creatinine, BUN, urea, or ureic acid, increased plasma glucose, and impaired glucose regulation. These changes were observed despite no difference in SCN Per2 or Bmal1 expression suggesting a working SCN (Mendez et al, 2016) -evidence of PLICCS with specific relevance to the peripheral clocks and systems.…”
Section: Overall Potential For the Validity Of Pliccsanimal Studies Cmentioning
confidence: 85%
See 1 more Smart Citation
“…Although melatonin is synthesized in human placenta since the first weeks and prevails during the whole pregnancy, maternal pineal melatonin, which readily crosses the placental barrier, seems to be the most important supply of this indoleamine for the fetus and has an important role in its development . In human fetal brain, melatonin receptors are widespread expressed at around 15 weeks of gestation, and nocturnal melatonin in the maternal serum reaches a peak during the third trimester of pregnancy .…”
Section: Discussionmentioning
confidence: 99%
“…These effects appear to be established in the first third (7 weeks) of pregnancy because differences were seen between CON and combined SSW groups. Maternal circadian disruption throughout pregnancy similarly increased the gestation length of rats by 12 h in the one rodent study to report precise timing of delivery (Mendez et al 2016). Interestingly, a study utilizing the National Danish Birth Cohort found that fixed night work increased the risk of post term birth (>41 weeks of gestation) in singleton human pregnancies (Zhu et al 2004b).…”
Section: Palmermentioning
confidence: 99%